Efikasi-Kendiri Pelajar Teknologi Automotif berdasarkan Standard Kemahiran Pekerjaan Kebangsaan di Kolej Vokasional - Haron, Mohamad Zhurad; Ahmad, Adnan (Online Journal for TVET Practitioners, 2018)
Self-efficacy is a medium in individual behaviour achievement and ability to complete task given with high desire. This paper is to discuss about the fundamental of self-efficacy in vocational and this research is focused on Automotive Technology. Research objective is to identify self-efficacy level based on National Occupational Skills Standard (NOSS), mastery experience, vicarious experiences, and verbal persuasion experience. Result shows high mean level in self-efficacy for NOSS Level 1, 2 and 3. While moderate mean level in mastery experience, vicarious and verbal persuasuion. Regression analysis showed that there is relationship in all three predictor variables with self-efficacy. In summary, students in Automotive Technology Course still need to increase their self-efficacy in order to prepare themselves to be skilled workers. Knowledge and skills blend with high level of self-efficacy to enhance teaching and learning strategies. The teaching practices which are able to increase the students’ self-efficacy were also identified.